Cathode for electrodialysis device, preparation method of cathode, electrodialysis device and application of electrodialysis device

By using a cathode made of three-dimensional graphene and hydrothermal treated composite metal aluminate in the electrodialysis device, the problem that existing electrodialysis methods require complex removal steps after lithium ion concentration is solved, achieving high efficiency and economical lithium extraction process.

CN119409293APending Publication Date: 2025-02-11BLUESTAR BEIJING CHEM MACHINERY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411544008.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing electrodialysis method requires complex removal steps after lithium ions concentration, and the operation is complicated and the number of monovalent selective ion exchange membranes is high, which is costly.

Method used

A cathode for an electrodialysis device is used, which includes three-dimensional graphene as a conductive substrate and a composite metal aluminate that has been treated with hydrothermal heat as the electrode material. This cathode simplifies the lithium extraction process by selectively adsorbing lithium ions and reduces the use of an ion exchange membrane.

Benefits of technology

The efficiency of lithium extraction is improved, the complexity of subsequent impurity removal steps is reduced, the cost of the electrodialysis process is reduced, and the cathode can be recycled after desorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409293A_ABST
    Figure CN119409293A_ABST
Patent Text Reader

Abstract

The invention relates to a cathode for an electrodialysis device, a preparation method of the cathode, the electrodialysis device and application of the electrodialysis device. The cathode for the electrodialysis device comprises a conductive substrate and an electrode material arranged on the surface of the conductive substrate. A conductive substrate is three-dimensional graphene, an electrode material is composite metal aluminate subjected to hydro-thermal treatment, and preparation raw materials of the composite metal aluminate comprise a soluble aluminum source, soluble salt and a precipitator. Wherein the cation of the soluble salt is any one of Mn < 2 + >, Mg < 2 + >, Na < + > and Ni < 2 + >. The composite metal aluminate subjected to hydrothermal treatment has relatively high selective adsorption capacity on lithium and can be uniformly distributed on the surface of the three-dimensional graphene. Therefore, after lithium in the salt lake brine is concentrated, lithium ions can be selectively adsorbed by adopting the cathode disclosed by the invention, and lithium extraction can be realized without complex impurity removal after concentration. And the use number of selective ion exchange membranes can be reduced, and the cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium extraction from salt lakes, and in particular to a cathode for an electrodialysis device and a preparation method thereof, an electrodialysis device and applications thereof. Background Art

[0002] Lithium resources include ore lithium resources and salt lake brine lithium resources. Among them, the mining and extraction of ore lithium resources is relatively easy. Although salt lake brine contains rich lithium resources, the notable feature of my country's salt lake brine lithium resources is the high magnesium-lithium ratio, which makes the extraction of lithium resources very difficult. The currently available methods for extracting lithium from salt lake brine include precipitation, adsorption, calcination leaching, and electrodialysis.

[0003] Among them, electrodialysis is a green process technology that extracts lithium through physical means, and is also a new research direction for lithium extraction from salt lakes. This process passes brine containing lithium salts through one or more stages of electrodialyzers, and uses a monovalent selective ion exchange membrane to circulate and concentrate lithium to obtain lithium-rich and low-magnesium brine.

[0004] Although the retention rate of monovalent selective ion exchange membranes for divalent and multivalent ions is significantly higher than that for monovalent ions, when lithium ions pass through the monovalent selective ion exchange membranes, other monovalent ions can also pass through the monovalent selective ion exchange membranes, and the monovalent selective ion exchange membranes cannot completely retain divalent and multivalent ions. Therefore, the existing electrodialysis technology can only achieve the concentration and partial purification of lithium ions through monovalent selective ion exchange membranes. The obtained lithium-rich and low-magnesium brine contains a variety of impurity ions, and complex deep impurity removal, refining and concentration are required to obtain Li 2 CO 3 or LiCl.

[0005] In addition, when the existing electrodialysis method is used to concentrate lithium, multiple monovalent selective ion exchange membranes need to be set up, which is relatively costly.

[0006] Therefore, it is necessary to reduce the complexity of operations after lithium concentration and reduce the number of ion exchange membranes used. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In order to solve the problems in the prior art that the electrodialysis method for lithium concentration requires a complex impurity removal step, the operation is cumbersome, and more ion exchange membranes are used, resulting in high costs, the present invention provides a cathode for an electrodialysis device and a preparation method thereof, an electrodialysis device and its application.

[0009] (II) Technical solution

[0010] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0011] A cathode for an electrodialysis device, comprising a conductive substrate and an electrode material arranged on the surface of the conductive substrate;

[0012] The conductive matrix is ​​three-dimensional graphene; the electrode material is a composite metal aluminate that has been hydrothermally treated, and the raw materials for preparing the composite metal aluminate include a soluble aluminum source, a soluble salt, and a precipitant; wherein the cation of the soluble salt is Mn 2+ Mg 2+ 、Na + And Ni 2+ Any one of .

[0013] The cathode for the electrodialysis device as described above, preferably, the molar ratio of the metal ions in the soluble salt to the aluminum ions in the soluble aluminum source is 1:4-3:1, and the precipitant is a mixture of sodium hydroxide and sodium carbonate, wherein the molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to aluminum ions in the soluble aluminum source is 8:1;

[0014] In the cathode for an electrodialysis device, the thickness of the electrode material is 1-2 mm.

[0015] In a second aspect, the present invention further provides a method for preparing the cathode for the electrodialysis device, comprising the following steps:

[0016] S1: performing two oxidation treatments on graphite powder to prepare three-dimensional graphene;

[0017] S2: preparing the three-dimensional graphene prepared in step S1 into a conductive substrate;

[0018] S3: preparing a first mixed solution with a soluble aluminum source, a soluble salt, a precipitant and water, and then heating the first mixed solution to obtain a composite metal aluminate; then hydrothermally treating the composite metal aluminate prepared in step S3, cooling and washing, to obtain a hydrothermally treated composite metal aluminate;

[0019] S4: The hydrothermally treated composite metal aluminate prepared in step S3 is mixed with a binder, a conductive material and a solvent to prepare a slurry, and then the slurry is coated on the surface of the conductive substrate prepared in step S2, and after drying, a cathode for an electrodialysis device is obtained.

[0020] In the method for preparing a cathode for an electrodialysis device as described above, preferably, the step S1 specifically comprises:

[0021] S11: Towards K 2 S 4 O8 and P 2 O 5 Concentrated sulfuric acid is added to the mixture, and graphite powder is added to the mixed system under stirring to carry out a first oxidation reaction. After the reaction is completed, the mixture is cooled, washed, and dried to obtain a pre-oxidized product;

[0022] S12: adding the pre-oxidized material into concentrated sulfuric acid, uniformly dispersing the pre-oxidized material, and then adding potassium permanganate for a second oxidation reaction. Then, adding the first portion of deionized water, heating and stirring, and sequentially adding hydrogen peroxide solution and the second portion of deionized water to obtain a crude product.

[0023] S13: extracting, washing, and drying the crude product to obtain three-dimensional graphene.

[0024] In the method for preparing a cathode for an electrodialysis device as described above, preferably, the step S2 specifically comprises:

[0025] S21: dissolving the first binder in an organic solvent to obtain a second mixed solution, then adding the three-dimensional graphene prepared in step S1 to the second mixed solution and stirring until the organic solvent is completely volatilized to obtain a solid precursor; wherein the first binder is ethyl cellulose and the organic solvent is acetone;

[0026] S22: placing the solid precursor in a protective atmosphere, heat treating it at 750-850° C. for 1.5-2.5 h, and obtaining a conductive matrix precursor after cooling;

[0027] S23: removing impurities, cleaning and drying the conductive substrate precursor to obtain a conductive substrate.

[0028] In the method for preparing a cathode for an electrodialysis device as described above, preferably, the step S3 specifically comprises:

[0029] S31: dissolving a soluble salt, a soluble aluminum source and a precipitant in water to obtain a first mixed solution; wherein the molar ratio of metal ions in the soluble salt to aluminum ions in the soluble aluminum source is 1:4-3:1, the precipitant is a mixture of sodium hydroxide and sodium carbonate, the molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to aluminum ions in the soluble aluminum source is 8:1;

[0030] S32: placing the first mixed solution prepared in step S31 at 90-100° C. for heating and reacting for 1.5-2.5 hours, and drying after the reaction to obtain a composite metal aluminate;

[0031] S33: Mix the composite metal aluminate prepared in step S3 with a sodium hydroxide solution, adjust the pH of the mixed system to 13-14, and then allow the mixed system to hydrothermally react at 150-170° C. for 18-30 hours, cool and wash to obtain a hydrothermally treated composite metal aluminate.

[0032] In the method for preparing a cathode for an electrodialysis device as described above, preferably, the step S4 specifically comprises:

[0033] S41: dissolving the second binder in a solvent to obtain a mixed solution, then adding the hydrothermally treated composite metal aluminate and the conductive material to the mixed solution, and stirring evenly to obtain a slurry; the mass ratio of the second binder, the conductive material and the hydrothermally treated composite metal aluminate is (1-2):(1-2):(8-10); wherein the second binder is polyvinylidene fluoride, the solvent is N-methylpyrrolidone, and the conductive material is carbon black;

[0034] S42: The slurry is evenly coated on the surface of the conductive substrate, and dried for 8-12 hours to obtain a cathode for an electrodialysis device.

[0035] In a third aspect, the present invention provides an electrodialysis device, comprising the cathode for an electrodialysis device described above or a cathode for an electrodialysis device prepared by the above preparation method.

[0036] The electrodialysis device as described above, preferably, further comprises an anode, a concentration chamber partition and a desalination chamber partition are arranged between the anode and the cathode, a cation exchange membrane and an anion exchange membrane are arranged on both sides of the concentration chamber partition, and an anion exchange membrane and a cation exchange membrane are arranged on both sides of the desalination chamber partition, and adjacent concentration chamber partitions and desalination chamber partitions share the same anion exchange membrane or cation exchange membrane;

[0037] The number of the concentration chamber partition and the number of the desalination chamber partition are both one.

[0038] In a fourth aspect, the present invention further provides an application of the cathode for an electrodialysis device as described above or the cathode for an electrodialysis device prepared by the above preparation method in extracting lithium from salt lake brine.

[0039] (III) Beneficial effects

[0040] The cathode for the electrodialysis device of the present invention uses three-dimensional graphene as a conductive matrix and a hydrothermally treated composite metal aluminate as an electrode material. The three-dimensional graphene has a huge specific surface area. The hydrothermally treated composite metal aluminate can be evenly distributed on the surface of the three-dimensional graphene, and the hydrothermally treated composite metal aluminate has a high selective adsorption capacity for lithium in salt lake brine.

[0041] Therefore, the cathode of the present invention is used in an electrodialysis device. After the selective ion exchange membrane concentrates lithium, the cathode can directly selectively adsorb lithium ions, thereby improving the efficiency of lithium extraction, so that the electrodialysis process can extract lithium without complicated impurity removal after concentration. In addition, when the electrodialysis process using the cathode of the present invention concentrates lithium in salt lake brine, it can reduce the large-scale use of monovalent selective ion exchange membranes and reduce the cost of the electrodialysis process. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The schematic diagram of the movement of ions in the electrodialysis device of the present invention;

[0043] Figure 2 It is a structural schematic diagram of an electrodialysis device in the prior art;

[0044] Figure 3a as well as Figure 3b This is a scanning electron microscope image of the cathode for the electrodialysis device prepared in Example 1;

[0045] Figure 4 The XRD spectrum of the hydrothermally treated composite metal aluminate prepared in Example 1-4;

[0046] Figure 5 XRD spectra of the composite metal aluminates prepared in Example 1 and Examples 7-9 after hydrothermal treatment;

[0047] Figure 6 A comparison chart of the adsorption capacity of lithium ions of the cathodes prepared in Examples 1-6 and Comparative Example 3 at different cycle times;

[0048] Figure 7 This is a comparison chart of the adsorption capacity of lithium ions of the cathodes prepared in Example 1 and Examples 7-9 at different cycle times;

[0049] Figure 8 This is a comparison chart of the adsorption capacity of lithium ions of the cathodes prepared in Example 1 and Comparative Example 1 at different cycle times;

[0050] Fig. 9 This is a comparison chart of the adsorption capacity of lithium ions of the cathodes prepared in Example 1 and Comparative Example 2 at different cycle times;

[0051] Fig.10 This is a schematic diagram of the change in the adsorption capacity of lithium ions of the cathode prepared in Example 1 at different cycle times;

[0052] Fig.11 This is a comparison chart of the adsorption capacity of lithium ions by cathodes of different thicknesses prepared in Example 1, Examples 10-12, and Comparative Examples 4-8.

[0053] [Description of Reference Numerals]

[0054] 1: anode; 2: cathode; 3: anode chamber; 4: cathode chamber; 5: cation exchange membrane; 6: anion exchange membrane; C1: concentrated solution inlet; C2: concentrated solution outlet; S1: desalted solution inlet; S2: desalted solution outlet; Y1: anode solution inlet; Y2: anode solution outlet; Y3: cathode solution inlet; Y4: cathode solution outlet. DETAILED DESCRIPTION

[0055] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with specific implementation methods and drawings.

[0056] The invention provides a cathode for an electrodialysis device, comprising a conductive substrate and an electrode material arranged on the surface of the conductive substrate.

[0057] The conductive matrix in the present invention is three-dimensional graphene, and the electrode material is a composite metal aluminate that has been subjected to hydrothermal treatment. The raw materials for preparing the composite metal aluminate include a soluble aluminum source, a soluble salt, and a precipitant, wherein the cation of the soluble salt is Mn 2+ Mg 2+ 、Na + And Ni 2+ Any one of .

[0058] Preferably, the molar ratio of the metal ions in the soluble salt of the present invention to the aluminum ions in the soluble aluminum source is 1:4-3:1, for example, it can be 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 1:3-3:1, 1:3-2:1, 1:2-2:1, etc., beyond this ratio range, for example, when it is 4:1, the selective adsorption capacity of the prepared composite metal aluminate for lithium ions will be significantly reduced. In the present invention, the precipitant includes a mixture of sodium hydroxide and sodium carbonate, wherein the molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to aluminum ions in the soluble aluminum source is 8:1. In addition, in the cathode for the electrodialysis device of the present invention, the thickness of the electrode material is 1-2mm, preferably 1.5mm. Specifically, when the thickness of the electrode material in the cathode for the electrodialysis device is 1-2mm, the potential difference of the electrode is small, especially at 1.5mm, the potential difference of the electrode is the smallest, the planning degree is the lowest, and the reversibility is the best. When the thickness of the electrode is too large or too small, the polarization degree will increase, because the mass transfer distance of lithium ions increases when lithium is inserted and deintercalated, which is not conducive to the lithium ion insertion and deintercalation and mass transfer process, thereby causing an increase in the degree of polarization.

[0059] The present invention uses three-dimensional graphene as a conductive matrix and a composite metal aluminate that has been subjected to hydrothermal treatment as an electrode material. The three-dimensional graphene has a huge specific surface area. The composite metal aluminate that has been subjected to hydrothermal treatment has a high selective adsorption capacity for lithium, and the composite metal aluminate that has been subjected to hydrothermal treatment is evenly distributed on the surface of the three-dimensional graphene. Therefore, the cathode of the present invention can be used in an electrodialysis device. After the selective ion exchange membrane concentrates the lithium, the cathode can directly selectively adsorb the lithium ions in the concentrated solution, which can improve the efficiency of lithium extraction, so that the electrodialysis process can extract lithium without complicated impurity removal after the selective ion exchange membrane concentrates the lithium ions, and only needs to desorb the cathode that has reached the saturated adsorption amount to achieve lithium purification. In addition, when the electrodialysis process using the cathode of the present invention concentrates lithium in salt lake brine, it can also reduce the number of monovalent selective ion exchange membranes used and reduce the cost of the electrodialysis process.

[0060] The present invention also provides a method for preparing the cathode for the electrodialysis device, comprising the following steps:

[0061] S1: oxidizing graphite powder twice to prepare three-dimensional graphene.

[0062] S2: Prepare the three-dimensional graphene prepared in step S1 into a conductive substrate.

[0063] S3: A soluble aluminum source, a soluble salt, a precipitant and water are prepared into a first mixed solution, and the first mixed solution is then heated to obtain a composite metal aluminate. The composite metal aluminate prepared in step S3 is then hydrothermally treated, cooled and washed to obtain a hydrothermally treated composite metal aluminate.

[0064] S4: The hydrothermally treated composite metal aluminate prepared in step S3 is mixed with a binder, a conductive material and a solvent to prepare a slurry, and then the slurry is coated on the surface of the conductive substrate prepared in step S2, and after drying, a cathode for an electrodialysis device is obtained.

[0065] Preferably, the above step S1 specifically includes:

[0066] S11: Towards K 2 S 4 O 8 and P 2 O 5 Concentrated sulfuric acid is added to the mixture, and graphite powder is added to the mixed system under stirring to carry out the first oxidation reaction. After the reaction is completed, it is cooled, washed, and dried to obtain a pre-oxidized product.

[0067] S12: adding the pre-oxidized material into concentrated sulfuric acid, uniformly dispersing the material, and then adding potassium permanganate for a second oxidation reaction. Then, adding the first portion of deionized water, heating and stirring, and sequentially adding hydrogen peroxide solution and the second portion of deionized water to obtain a crude product.

[0068] S13: extracting, washing, and drying the crude product to obtain three-dimensional graphene.

[0069] In the above step S11, graphite powder: K 2 S 4 O 8 :P 2 O 5 The mass ratio is (2-4):(3-6):(3-6), K 2 S 4 O 8 The mass volume ratio w:v with concentrated sulfuric acid is 1:5-1:6, and the first oxidation reaction is carried out in a water bath at 70-90°C for 5-7 hours. The particle size of the graphite powder selected in step S11 is preferably 400 mesh or above. The graphite powder within this particle size range is smaller in size, and the prepared three-dimensional graphene has better dispersibility.

[0070] Specifically, in step S11, K 2 S 4 O 8 and P 2 O 5 The two solid powders are poured into a reaction vessel, such as a three-necked flask, and then concentrated sulfuric acid of the corresponding proportion is quickly poured into the reaction vessel at one time, and the temperature of the constant temperature water bath device, such as a constant temperature water bath pot, is set to 70-90°C, and the mixture in the reaction vessel is stirred at the same time. Then the graphite powder is slowly, a small amount, and repeatedly added to the above-mentioned mixed system. In this process, it is necessary to avoid the graphite powder from being stained on the wall of the reaction vessel to avoid the graphite powder from participating in the reaction. And the reaction needs to be stirred continuously during the entire reaction process. After the reaction is completed, it is cooled to room temperature, and the material in the reaction vessel is poured into a Buchner funnel, and a vacuum circulating water pump is used for suction filtration. The filter cake is washed with deionized water until the pH value of the filtrate reaches 6.5-7.5, preferably 7. After the suction filtration is completed, the filter cake is dried at room temperature for 24 hours to obtain a pre-oxidized compound.

[0071] In step S12, the pre-oxidant is added to concentrated sulfuric acid under ice bath conditions, and then potassium permanganate is continuously added, and the system is heated to 30-40°C for secondary oxidation reaction for 1.5-2.5h. After the reaction is fully completed, the first portion of deionized water is added several times, and after stirring for a certain period of time, hydrogen peroxide solution and the second portion of deionized water are added in sequence to stop the secondary oxidation reaction to obtain a crude product. Among them, the mass volume ratio w:v of the pre-oxidant and concentrated sulfuric acid is 1:8-1:10, the mass volume ratio of potassium permanganate to concentrated sulfuric acid is 1:6-1:10, the volume ratio of the first portion of deionized water to concentrated sulfuric acid is 1.5-2.5, and the volume ratio of hydrogen peroxide solution, the second portion of deionized water and concentrated sulfuric acid is (20-30):(1300-1500):(200-250).

[0072] Specifically, in step S12, concentrated sulfuric acid is added to a reaction vessel, such as a three-necked flask, under ice bath conditions. Before adding concentrated sulfuric acid, it is necessary to ensure that the reaction vessel is dry to avoid heat release after adding concentrated sulfuric acid. After adding concentrated sulfuric acid, continue to slowly add pre-oxide to the reaction vessel, keep the temperature below 20 ° C, stir for 1h, and make the pre-oxide uniformly dispersed in concentrated sulfuric acid. After the pre-oxide is uniformly dispersed, potassium permanganate of the corresponding proportion is slowly added several times, and the addition amount of potassium permanganate is 3-5g / time. After all potassium permanganate is added to the reaction vessel, the solution system begins to gradually become viscous, and the system is heated to 30-40 ° C and then the secondary oxidation reaction is 1.5-2.5h. After the secondary oxidation reaction is fully completed, the first portion of deionized water is added to the reaction vessel several times, and then the system is quickly heated to about 98 ° C. After stirring for 10-20min, a hydrogen peroxide solution with a mass fraction of 30% is added to the reaction vessel under stirring conditions, and then the entire system can be transferred to a container of a larger volume, and then the second portion of deionized water is added to the system, and the reaction stops. Alternatively, a second portion of deionized water may be added directly to the reaction vessel.

[0073] In step S13, the product is washed and filtered with a mixture of water and hydrochloric acid in a volume ratio of 8:1-12:1, and then washed with deionized water until neutral, and then dried to obtain a three-dimensional graphene with a three-dimensional structure. The three-dimensional graphene can be configured into a solution with deionized water or the like by combining ultrasonic dispersion or the like to obtain a solution in which the three-dimensional graphene is uniformly dispersed for standby use.

[0074] Preferably, the above step S2 specifically includes:

[0075] S21: dissolving the first binder in an organic solvent to obtain a second mixed solution, then adding the three-dimensional graphene dispersion prepared in step S14 to the second mixed solution and stirring until the organic solvent is completely volatilized to obtain a solid precursor. The first binder may be ethyl cellulose, and the organic solvent may be acetone.

[0076] S22: placing the solid precursor in a protective atmosphere, for example, in a tube furnace, heating the temperature to 750-850° C. at a heating rate of 10-12° C. / min, keeping the temperature for 1.5-2.5 hours, and obtaining a conductive matrix precursor after cooling.

[0077] S23: Using a hydrochloric acid solution of a certain concentration, such as a 6 mol / L hydrochloric acid solution, the conductive matrix precursor is stirred at room temperature for a certain time, such as 48 hours, to remove unreacted substances, and then filtered, and then washed with deionized water and ethanol for 3 times respectively, and then dried at a low temperature, such as 6°C, for a certain time, such as 12 hours, to obtain a conductive matrix.

[0078] Preferably, the above step S3 specifically includes:

[0079] S31: dissolving a soluble salt, a soluble aluminum source and a precipitant in water to obtain a first mixed solution. The molar ratio of the metal ions in the soluble salt to the aluminum ions in the soluble aluminum source is 1:4-3:1, for example, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 1:3-3:1, 1:3-2:1, 1:2-2:1, etc. The precipitant is a mixture of sodium hydroxide and sodium carbonate, the molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to aluminum ions in the soluble aluminum source is 8:1. In this step, the cation of the soluble salt is Mn 2+ Mg 2+ 、Na + And Ni 2+ Any of the above, the anions of the soluble salts include but are not limited to Cl - 、SO 4 2- 、NO 3 - etc. The aluminum source can be AlCl 3 、Al 2 (SO 4 ) 3 wait.

[0080] S32: The first mixed solution prepared in step S31 is loaded into a reactor, and heated at 90-100° C. under normal pressure for reaction for 1.5-2.5 hours. After the reaction is completed, the suspension is precipitated and cooled, and then dried to obtain a composite metal aluminate.

[0081] S33: The composite metal aluminate prepared in step S3 is mixed with a sodium hydroxide solution in a hydrothermal kettle, the pH of the mixed system is adjusted to 13-14, and then the mixed system is subjected to a hydrothermal reaction at 150-170°C for 18-30h, cooled to room temperature and then dried, for example, at 6°C for 12h, and then washed with deionized water and ethanol to remove unreacted sodium hydroxide, to obtain a hydrothermally treated composite metal aluminate.

[0082] The chemical equation for the reaction in step S32 is:

[0083] 6X 2+ +2Al 3+ +16OH - +CO 3 2- +4H 2 O→X 6 Al 2 (OH) 16 CO 3 ·4H 2 O, or:

[0084] 12X + +2Al 3+ +16OH - +CO 3 2- +4H 2 O→X 12 Al 2 (OH) 16 CO 3 ·4H 2 O

[0085] Where X 2+ or X + It is a cation in a soluble salt.

[0086] The present invention adjusts the crystal structure, crystal morphology and grain purity of the composite metal aluminate by hydrothermally reacting the composite metal aluminate with a sodium hydroxide solution, so that the grains grow further uniformly, and metastable or other special condensed compounds or new compounds are generated during the hydrothermal treatment process, thereby achieving uniform doping of the material, introducing new ions, increasing the electronic structure and surface active sites of the composite metal aluminate, and being able to directly affect the adsorption and desorption process of lithium ions, thereby increasing the selective adsorption performance of the composite metal aluminate for lithium ions. Therefore, compared with the composite metal aluminate that has not been hydrothermally treated, the composite metal aluminate that has been hydrothermally treated has a significantly improved selective adsorption capacity for lithium ions.

[0087] Preferably, the above step S4 specifically includes:

[0088] S41: dissolving the second binder in a solvent to obtain a mixed solution, then adding the composite metal aluminate and the conductive material that have been subjected to the hydrothermal treatment to the mixed solution, stirring evenly to obtain a slurry, wherein the mass ratio of the second binder, the conductive material and the composite metal aluminate that have been subjected to the hydrothermal treatment is (1-2):(1-2):(8-10), preferably 1:1:8. The second binder is polyvinylidene fluoride (PVDF), the solvent is N-methylpyrrolidone (NMP), and the conductive material is carbon black.

[0089] S42: The slurry is evenly coated on the surface of the conductive substrate, and dried for 8-12 hours to obtain a cathode for an electrodialysis device.

[0090] The present invention also provides an electrodialysis device, including a cathode and an anode, with a concentration chamber partition and a desalination chamber partition arranged between the anode and the cathode. A cation exchange membrane and an anion exchange membrane are respectively arranged on both sides of the concentration chamber partition, and an anion exchange membrane and a cation exchange membrane are respectively arranged on both sides of the desalination chamber partition, and adjacent concentration chamber partitions and desalination chamber partitions share the same anion exchange membrane or cation exchange membrane. The middle parts of the concentration chamber partition and the desalination chamber partition are hollowed out, and the hollowed-out part in the middle of the concentration chamber partition forms a concentration chamber with the anion exchange membrane and the cation exchange membrane on both sides thereof, and the hollowed-out part in the middle of the desalination chamber partition forms a desalination chamber with the anion exchange membrane and the cation exchange membrane on both sides thereof. In the present invention, the number of concentration chamber partitions and desalination chamber partitions is 1 each. Preferably, the anode in the present invention can adopt a titanium-plated ruthenium-iridium electrode, which has good corrosion resistance and conductivity. The electrodialysis device of the present invention can use a DC power supply to provide an electric field force, such as Figure 1 As shown, under the action of the external electric field force, cations gradually move toward the cathode through the cation exchange membrane, and anions gradually move toward the anode through the anion exchange membrane. The circulation of solutions such as electrode solution, concentrated solution and desalted solution can be achieved by a peristaltic pump.

[0091] like Figure 2As shown, the electrodialysis device in the prior art includes a cathode 2 and an anode 1, a cathode chamber 4 is arranged near the cathode 2, an anode chamber 3 is arranged near the anode 1, a cathode liquid inlet Y3 and a cathode liquid outlet Y4 are provided on the cathode chamber 4, and an anode liquid inlet Y1 and an anode liquid outlet Y2 are provided on the anode chamber 3. A plurality of alternating concentration chambers and desalination chambers are provided between the cathode 2 and the anode 1, wherein a cation exchange membrane 5 and an anion exchange membrane 6 are provided on both sides of the concentration chamber and the desalination chamber, respectively, and adjacent concentration chambers and desalination chambers share a cation exchange membrane or a common anion exchange membrane, and a concentrated liquid inlet C1 and a concentrated liquid outlet C2 are provided at both ends of each concentration chamber, and similarly, a desalination liquid inlet S1 and a desalination liquid outlet S2 are provided at both ends of each desalination chamber. In the existing electrodialysis device, a plurality of concentration chamber partitions and a plurality of desalination chamber partitions are required to form a plurality of concentration chambers and a plurality of desalination chambers, and a large number of ion exchange membranes are provided to achieve effective concentration of lithium ions. However, in the present invention, the number of the concentration chamber partition and the desalination chamber partition are both one, that is, a total of three ion exchange membranes are arranged. Specifically, the anion exchange membrane is fixed in the middle, and cation exchange membranes are arranged on both sides to realize lithium extraction from the salt lake, which can reduce the use of ion exchange membranes and reduce costs.

[0092] In addition, the present invention also provides an application of the above-mentioned cathode for electrodialysis device or the cathode for electrodialysis device prepared by the above-mentioned preparation method in extracting lithium from salt lake brine. The electrodialysis device of the present invention is applied to extracting lithium from salt lake brine, and the lithium ions in the salt lake brine can be selectively adsorbed by the cathode in the electrodialysis device after simple concentration through the ion exchange membrane. After the cathode reaches saturated lithium adsorption, only desorption treatment is required to achieve lithium purification, and the cathode can be recycled after desorption.

[0093] Example 1

[0094] This embodiment provides a method for preparing a cathode for an electrodialysis device, comprising the following steps:

[0095] S1: K 2 S 4 O 8 and P 2 O 5 Pour into a three-necked flask, then quickly pour concentrated sulfuric acid into the three-necked flask, then set the temperature of the constant temperature water bath to 80°C, stir the mixture in the reaction vessel, and then slowly, small amounts, and multiple times add graphite powder to the three-necked flask, and continue stirring and reacting for 6 hours. After the reaction is completed, cool to room temperature, pour the contents of the three-necked flask into a Buchner funnel, repeatedly filter and wash the filter cake with deionized water until the pH value of the filtrate reaches 7, then dry the filter cake at room temperature for 24 hours to obtain a pre-oxidized compound. Graphite powder: K 2 S 4O 8 :P 2 O 5 The mass ratio of K is 1:1:1, 2 S 4 O 8 The mass volume ratio w:v with concentrated sulfuric acid is 1:6. The particle size of the graphite powder selected in this embodiment is 500 mesh.

[0096] Add concentrated sulfuric acid to a three-necked flask under ice bath conditions, then continue to slowly add pre-oxidant to the three-necked flask, keep the temperature below 20°C and stir for 1h, then slowly add potassium permanganate several times, each time adding 4g, and after all the potassium permanganate is added to the reaction vessel, the secondary oxidation reaction is 2h. After the reaction time is reached, add the first portion of deionized water to the three-necked flask several times, stir for 15min, continue stirring and add a 30% mass fraction of hydrogen peroxide solution to the three-necked flask, then transfer the entire system to a beaker with a larger volume, add the second portion of deionized water, and stop the reaction. In the secondary oxidation stage, the mass volume ratio w:v of the pre-oxidant and concentrated sulfuric acid is 1:9, the mass volume ratio of potassium permanganate and concentrated sulfuric acid is 1:8, the volume ratio of the first portion of deionized water to concentrated sulfuric acid is 2, and the volume ratio of hydrogen peroxide solution, the second portion of deionized water and concentrated sulfuric acid is 25:1400:230. After the reaction is stopped, the crude product is washed by suction, and then the product is washed and filtered with a mixture of water and hydrochloric acid in a volume ratio of 10:1, and then the filter cake is washed with deionized water until it is neutral and dried to obtain three-dimensional graphene. The three-dimensional graphene is configured into a three-dimensional graphene dispersion liquid using deionized water or the like through ultrasonic dispersion treatment.

[0097] S2: Ethyl cellulose is dissolved in acetone to obtain a second mixed solution, and then the three-dimensional graphene dispersion is added to the second mixed solution and stirred until the acetone is completely volatilized to obtain a solid precursor. The solid precursor is placed in a tube furnace, heated to 800°C at a heating rate of 10°C / min, kept warm for 2 hours, and cooled to obtain a conductive matrix precursor. The conductive matrix precursor is stirred with a hydrochloric acid solution at room temperature for 48 hours, then filtered, and then washed with deionized water and ethanol for 3 times respectively, and then dried at 6°C for 12 hours to obtain a conductive matrix.

[0098] S3: MnSO 4 、AlCl 3 , sodium hydroxide and sodium carbonate are dissolved in water to obtain a first mixed solution. 2+ With Al 3+ The molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to Al 3+The molar ratio is 8:1. The first mixed solution is loaded into a reactor, heated at 100°C under normal pressure for 2 hours, cooled and dried after the reaction is completed to obtain a composite metal aluminate. Then, the composite metal aluminate and the sodium hydroxide solution are mixed in a hydrothermal kettle, the pH of the mixed system is adjusted to 14, and then hydrothermally reacted at 160°C for 24 hours. After the reaction is completed, it is cooled to room temperature, then dried, and then washed with deionized water and ethanol to obtain a hydrothermally treated composite metal aluminate.

[0099] S4: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to obtain a mixed solution, then add the hydrothermally treated composite metal aluminate and carbon black to the mixed solution, stir evenly to obtain a slurry, the mass ratio of polyvinylidene fluoride, carbon black and the hydrothermally treated composite metal aluminate is 1:1:8. The slurry is evenly coated on the surface of the conductive substrate, and after drying for 12 hours, a cathode for an electrodialysis device is obtained, wherein the thickness of the electrode material is 1.5 mm.

[0100] Example 2-Example 6

[0101] Examples 2 to 6 are based on Example 1, except that Mn in Example 1 2+ With Al 3+ The molar ratios were changed to 1:4, 1:3, 1:2, 2:1 and 3:1 respectively.

[0102] Example 7

[0103] This embodiment provides a method for preparing a cathode for an electrodialysis device, comprising the following steps:

[0104] S1: K 2 S 4 O 8 and P 2 O 5 Pour into a three-necked flask, then quickly pour concentrated sulfuric acid into the three-necked flask, then set the temperature of the constant temperature water bath to 70°C, stir the mixture in the reaction vessel, and then slowly, small amounts, and multiple times add graphite powder to the three-necked flask, and continue stirring to react for 7 hours. After the reaction is completed, cool to room temperature, pour the contents of the three-necked flask into a Buchner funnel, repeatedly filter and wash the filter cake with deionized water until the pH value of the filtrate reaches 7, then dry the filter cake at room temperature for 24 hours to obtain a pre-oxidized compound. Graphite powder: K 2 S 4 O 8 :P 2 O 5 The mass ratio of K is 4:6:3, 2 S 4 O 8The mass volume ratio w:v with concentrated sulfuric acid is 1:5. The particle size of the graphite powder selected in this embodiment is 450 mesh.

[0105] Add concentrated sulfuric acid to the three-necked flask under ice bath conditions, then continue to slowly add the pre-oxidant to the three-necked flask, keep the temperature below 20°C and stir for 1h, then slowly add potassium permanganate several times, each time adding 5g, and after all the potassium permanganate is added to the reaction vessel, the secondary oxidation reaction is 2.5h. After the reaction time is reached, add the first portion of deionized water to the three-necked flask several times, stir for 15min, continue stirring and add a 30% mass fraction of hydrogen peroxide solution to the three-necked flask, then transfer the entire system to a beaker with a larger volume, add the second portion of deionized water, and stop the reaction. In the secondary oxidation stage, the mass volume ratio of the pre-oxidant to concentrated sulfuric acid is 1:10, the mass volume ratio of potassium permanganate to concentrated sulfuric acid is 1:6, the volume ratio of the first portion of deionized water to concentrated sulfuric acid is 1.5, and the volume ratio of hydrogen peroxide solution, the second portion of deionized water and concentrated sulfuric acid is 20:1300:200. After the reaction stops, the crude product is washed with suction, and then the product is washed and filtered with a mixture of water and hydrochloric acid in a volume ratio of 8:1, and then the filter cake is washed with deionized water until it is neutral and dried to obtain three-dimensional graphene. The three-dimensional graphene is configured into a three-dimensional graphene dispersion liquid using deionized water or the like through ultrasonic dispersion treatment.

[0106] S2: Ethyl cellulose is dissolved in acetone to obtain a second mixed solution, and then the three-dimensional graphene dispersion is added to the second mixed solution and stirred until the acetone is completely volatilized to obtain a solid precursor. The solid precursor is placed in a tube furnace, heated to 750°C at a heating rate of 12°C / min, kept warm for 2.5 hours, and cooled to obtain a conductive matrix precursor. The conductive matrix precursor is stirred with a hydrochloric acid solution at room temperature for 48 hours, then filtered, and then washed with deionized water and ethanol three times respectively, and then dried at 6°C for 12 hours to obtain a conductive matrix.

[0107] S3: MgSO 4 、AlCl 3 , sodium hydroxide and sodium carbonate are dissolved in water to obtain a first mixed solution. 2+ With Al 3+ The molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to Al 3+The molar ratio is 8:1. The first mixed solution is loaded into a reactor, heated at 90°C under normal pressure for 2.5 hours, cooled and dried after the reaction to obtain a composite metal aluminate. Then, the composite metal aluminate and the sodium hydroxide solution are mixed in a hydrothermal kettle, the pH of the mixed system is adjusted to 13, and then hydrothermally reacted at 150°C for 30 hours. After the reaction, it is cooled to room temperature, dried, and then washed with deionized water and ethanol to obtain a hydrothermally treated composite metal aluminate.

[0108] S4: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to obtain a mixed solution, then add the hydrothermally treated composite metal aluminate and carbon black to the mixed solution, stir evenly to obtain a slurry, the mass ratio of polyvinylidene fluoride, carbon black and the hydrothermally treated composite metal aluminate is 2:2:10. The slurry is evenly coated on the surface of the conductive substrate, and after drying for 10 hours, a cathode for an electrodialysis device is obtained, wherein the thickness of the electrode material is 1.5 mm.

[0109] Example 8

[0110] This embodiment provides a method for preparing a cathode for an electrodialysis device, comprising the following steps:

[0111] S1: K 2 S 4 O 8 and P 2 O 5 Pour into a three-necked flask, then quickly pour concentrated sulfuric acid into the three-necked flask, then set the temperature of the constant temperature water bath to 90°C, stir the mixture in the reaction vessel, and then slowly, in small amounts, add graphite powder to the three-necked flask several times, and continue stirring to react for 5 hours. After the reaction is completed, cool to room temperature, pour the contents of the three-necked flask into a Buchner funnel, repeatedly filter and wash the filter cake with deionized water until the pH value of the filtrate reaches 7, then dry the filter cake at room temperature for 24 hours to obtain a pre-oxidized compound. Graphite powder: K 2 S 4 O 8 :P 2 O 5 The mass ratio of K is 2:3:6, 2 S 4 O 8 The mass volume ratio w:v with concentrated sulfuric acid is 1:5.5. The particle size of the graphite powder selected in this embodiment is 400 mesh.

[0112] Add concentrated sulfuric acid to a three-necked flask under ice bath conditions, then continue to slowly add pre-oxidant to the three-necked flask, keep the temperature below 20°C and stir for 1h, then slowly add potassium permanganate several times, each time adding 3g, and after all the potassium permanganate is added to the reaction vessel, the secondary oxidation reaction is 1.5h. After the reaction time is reached, add the first portion of deionized water to the three-necked flask several times, stir for 15min, continue stirring and add a 30% mass fraction of hydrogen peroxide solution to the three-necked flask, then transfer the entire system to a beaker with a larger volume, add the second portion of deionized water, and stop the reaction. In the secondary oxidation stage, the mass volume ratio w:v of the pre-oxidant and concentrated sulfuric acid is 1:8, the mass volume ratio of potassium permanganate and concentrated sulfuric acid is 1:10, the volume ratio of the first portion of deionized water to concentrated sulfuric acid is 2.5, and the volume ratio of hydrogen peroxide solution, the second portion of deionized water and concentrated sulfuric acid is 30:1500:250. After the reaction is stopped, the crude product is washed with suction, and then the product is washed and filtered with a mixture of water and hydrochloric acid in a volume ratio of 12:1, and then the filter cake is washed with deionized water until it is neutral and dried to obtain three-dimensional graphene. The three-dimensional graphene is configured into a three-dimensional graphene dispersion liquid using deionized water or the like through ultrasonic dispersion treatment.

[0113] S2: Ethyl cellulose is dissolved in acetone to obtain a second mixed solution, and then the three-dimensional graphene dispersion is added to the second mixed solution and stirred until the acetone is completely volatilized to obtain a solid precursor. The solid precursor is placed in a tube furnace, heated to 850°C at a heating rate of 11°C / min, kept warm for 1.5 hours, and cooled to obtain a conductive matrix precursor. The conductive matrix precursor is stirred with a hydrochloric acid solution at room temperature for 48 hours, then filtered, and then washed with deionized water and ethanol three times respectively, and then dried at 6°C for 12 hours to obtain a conductive matrix.

[0114] S3: NiSO 4 、AlCl 3 , sodium hydroxide and sodium carbonate are dissolved in water to obtain a first mixed solution. 2+ With Al 3+ The molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to Al 3+ The molar ratio is 8:1. The first mixed solution is loaded into a reactor, heated at 95°C under normal pressure for 1.5 hours, cooled and dried after the reaction, to obtain a composite metal aluminate. Then, the composite metal aluminate and the sodium hydroxide solution are mixed in a hydrothermal kettle, the pH of the mixed system is adjusted to 13.5, and then hydrothermally reacted at 170°C for 18 hours. After the reaction, it is cooled to room temperature, dried, and then washed with deionized water and ethanol to obtain a hydrothermally treated composite metal aluminate.

[0115] S4: Dissolve polyvinylidene fluoride in N-methylpyrrolidone to obtain a mixed solution, then add the hydrothermally treated composite metal aluminate and carbon black to the mixed solution, stir evenly to obtain a slurry, the mass ratio of polyvinylidene fluoride, carbon black and the hydrothermally treated composite metal aluminate is 1.5:1.5:9. The slurry is evenly coated on the surface of the conductive substrate, and after drying for 8 hours, a cathode for an electrodialysis device is obtained, wherein the thickness of the electrode material is 1.5 mm.

[0116] Example 9

[0117] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the metal salt in step S3 is NaCl and the aluminum source is Al 2 (SO 4 ) 3 , Na + With Al 3+ The molar ratio is 1:1.

[0118] Example 10

[0119] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 1.19 mm.

[0120] Embodiment 11

[0121] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 1.78 mm.

[0122] Example 12

[0123] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 2.0 mm.

[0124] Comparative Example 1

[0125] This comparative example provides a method for preparing a cathode for an electrodialysis device, which differs from Example 1 in that step S1 is omitted, and the three-dimensional graphene dispersion in step S2 is replaced with a two-dimensional graphene dispersion (i.e., a dispersion of single-layer graphene).

[0126] Comparative Example 2

[0127] This comparative example provides a method for preparing a cathode for an electrodialysis device, which is different from Example 1 in that after the composite metal aluminate is prepared in step S3, it is no longer mixed with sodium hydroxide for hydrothermal treatment.

[0128] Comparative Example 3

[0129] This comparative example provides a method for preparing a cathode for an electrodialysis device, which is different from Example 1 in that in step S3, Mn 2+ With Al 3+ The molar ratio is 4:1.

[0130] Comparative Example 4

[0131] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 0 mm.

[0132] Comparative Example 5

[0133] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 0.45 mm.

[0134] Comparative Example 6

[0135] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 0.8 mm.

[0136] Comparative Example 7

[0137] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 2.5 mm.

[0138] Comparative Example 8

[0139] This embodiment provides a method for preparing a cathode for an electrodialysis device. The difference from Embodiment 1 is that the thickness of the electrode material in the cathode for the electrodialysis device is 3.0 mm.

[0140] Figure 3a as well as Figure 3b The electron microscope images of the cathode for the electrodialysis device prepared in Example 1 at different magnifications are shown in FIG. Figure 3a as well as Figure 3b It can be seen that the composite material of the hydrothermally treated composite metal aluminate and three-dimensional graphene has a three-dimensional structure, and the hydrothermally treated composite metal aluminate can be evenly distributed on the surface of the three-dimensional graphene.

[0141] The composite metal aluminates prepared in Example 1, Example 2, Example 3 and Example 4 after hydrothermal treatment were subjected to XRD detection, and the results were as follows: Figure 4 Spectrum shown.

[0142] The XRD curves of the composite metal aluminates prepared in Examples 7, 8 and 9 after hydrothermal treatment were compared with the XRD curves of the composite metal aluminates prepared in Example 1 after hydrothermal treatment. Figure 5 Spectrum shown.

[0143] pass Figure 4 It can be seen that the XRD curves of the composite metal aluminates prepared by Example 1, Example 2, Example 3 and Example 4 after hydrothermal treatment are consistent. Figure 5 It can be seen that the XRD curves of the hydrothermally treated composite metal aluminates prepared in Examples 7, 8 and 9 are similar to the XRD curve of the hydrothermally treated composite metal aluminates prepared in Example 1, indicating that the structures of the hydrothermally treated composite metal aluminates are consistent / similar, and no alienated structures are produced, but peaks are produced at 2θ=10° and 2θ=20°.

[0144] The cathodes prepared in Examples 1-6 and Comparative Example 3 were used for Li + Specifically, the cathode prepared in Examples 1-6 and Comparative Example 3 was used to form an electrodialysis device, which was operated in a constant voltage mode of 0.5 V of a DC power supply to perform an adsorption and desorption cycle, and the adsorption capacity of the cathode for lithium ions each time was measured to obtain Figure 6 .pass Figure 6 It can be seen that the cathodes of Examples 1-6 have a high adsorption capacity for lithium ions, and after 40 regeneration cycles of the cathodes of Examples 1-6, as the lithium extraction cycle increases, the adsorption capacity of each cathode for lithium ions remains at a high level, indicating that the cathodes prepared in Examples 1-6 have good lithium extraction capabilities. However, the adsorption capacity of the cathodes prepared in Comparative Example 3 for lithium ions is significantly lower than that of Examples 1-6. In addition, in general, aluminum is more selective for lithium and is more likely to form complexes with lithium. Therefore, in general, the higher the ratio of aluminum atoms in soluble salts to soluble aluminum sources, the higher the lithium extraction efficiency of the prepared composite metal aluminate. However, the bonds between aluminum atoms are different, and some cations in metal salts are required as bearing connecting atoms to form chemical bonds with aluminum to form stable metal single atom sites. Therefore, it is not actually the case that the larger the proportion of aluminum, the better, but there is a Figure 6 When manganese:aluminum = 1:1, the lithium extraction effect of composite metal aluminate is best.

[0145] The cathode prepared in Examples 7-9 was used for Li +Similarly, the cathode prepared in Examples 7-9 was placed in a lithium ion salt solution of a certain concentration for 12 hours, and then desorbed. The adsorption capacity of the cathode for lithium ions was measured each time and compared with that in Example 1. Figure 7 .pass Figure 7 It can be seen that the cathodes of Examples 7-9 also have a high adsorption capacity for lithium ions, and after 40 regeneration cycles of the cathodes of Examples 7-9, the adsorption capacity of lithium ions of each cathode is still maintained at a high level, indicating that the cathodes prepared in Examples 7-9 also have good lithium extraction capabilities.

[0146] The cathodes prepared in Example 1 and Comparative Example 1 were used in the same manner to + The adsorption of Figure 8 .like Figure 8 As shown, after the three-dimensional graphene is replaced by two-dimensional graphene in Comparative Example 1, the lithium ion adsorption capacity of the cathode is significantly reduced. Figure 8 It can be seen that the lithium extraction ability of the composite metal aluminate attached to three-dimensional graphene is significantly better than that of the composite metal aluminate attached to two-dimensional graphene. The reason may be that two-dimensional graphene is composed of a single layer of carbon atoms interconnected into a hexagonal grid. Although the unique sandwich structure of two-dimensional graphene is conducive to the rapid transfer of ions, its theoretical specific surface area is as high as 600m 2 / g, but two-dimensional graphene still has problems such as contact between adjacent graphene layers and aggregation of graphene sheets, so the adsorption performance of composite metal aluminates attached to two-dimensional graphene for lithium ions is not as ideal as that of three-dimensional graphene. The three-dimensional graphene prepared by the present invention shows a 934.9m 2 / g specific surface area, this hierarchical porous structure can avoid the problems of interlayer contact and aggregation of two-dimensional graphene, so the selective adsorption capacity of lithium ions by the composite metal aluminate attached to the two-dimensional graphene is significantly improved.

[0147] The cathodes prepared in Example 1 and Comparative Example 2 were used in the same manner to + The adsorption of Fig. 9 .like Fig. 9 As shown, in Comparative Example 2, the composite metal aluminate was not subjected to hydrothermal treatment, and the lithium ion adsorption capacity of the prepared cathode was significantly reduced.

[0148] Furthermore, the cathode prepared in Example 1 was subjected to 100 cycles of adsorption test, and the results were Fig.10 ,pass Fig.10 It can be seen that even after 100 cycles, the adsorption capacity of the cathode of Example 1 for lithium ions is still maintained at a high level.

[0149] The cathode prepared in Example 1 is used in an electrodialysis device. In addition to the above-mentioned cathode, the electrodialysis device also includes an anode, and a concentration chamber partition and a desalination chamber partition are arranged between the anode and the cathode. An anion exchange membrane is arranged on the side of the concentration chamber partition facing the cathode, and an anion exchange membrane is arranged on the side of the desalination chamber partition facing the anode, and the sides opposite to the concentration chamber partition and the desalination chamber partition share the same cation exchange membrane. The middle parts of the concentration chamber partition and the desalination chamber partition are both hollowed out, and the hollow part in the middle of the concentration chamber partition and the ion exchange membranes on both sides thereof form a concentration chamber, and the hollow part in the middle of the desalination chamber partition and the ion exchange membranes on both sides thereof form a desalination chamber.

[0150] Salt lake brine with a concentration of 30 mg / L was added to the desalination chamber, deionized water was added to the concentration chamber, and the circulation flow rate of the solution in the desalination chamber, the anode chamber of the concentration chamber, and the cathode chamber was set to 100 mL / min by a peristaltic pump. The electrodialysis device was operated in a constant voltage mode of 0.5 V of a DC power supply. Before applying voltage, the solution in each chamber was circulated for 15 minutes using a peristaltic pump to allow the circulation flow rate of the solution to reach a stable state, and then the DC power supply was switched to a constant voltage mode to start operation. The conductivity change of the desalination chamber was detected in real time using a conductivity meter, the volume of the desalination chamber was recorded every 30 minutes, and 1 mL of the supernatant sample in the desalination chamber was taken for ICP detection, and the lithium ion concentration in the desalination chamber was recorded in real time to obtain Table 1.

[0151] Table 1 Lithium ion concentration variation in the desalination chamber of the electrodialysis device assembled in Example 1

[0152] Time (h) element Content (mg / L) 0 <![CDATA[Li + ]]> 30 0.5 <![CDATA[Li + ]]> 29 1.0 <![CDATA[Li + ]]> 25 1.5 <![CDATA[Li + ]]> 26 2.0 <![CDATA[Li + ]]> 23 2.5 <![CDATA[Li + ]]> 20 3.0 <![CDATA[Li + ]]> 19 3.5 <![CDATA[Li + ]]> 15 4.0 <![CDATA[Li + ]]> 13 4.5 <![CDATA[Li + ]]> 8 5.0 <![CDATA[Li + ]]> 8 5.5 <![CDATA[Li + ]]> 8 6.0 <![CDATA[Li + ]]> 8

[0153] It can be seen from Table 1 that the cathode prepared in Example 1 can be used in an electrodialysis device to extract lithium from salt lake brine.

[0154] The adsorption capacity of lithium ions of the cathodes prepared in Example 1, Examples 10-12, and Comparative Examples 4-8 was measured, and then plotted to obtain Fig.11 .pass Fig.11 It can be seen that when the thickness of the electrode material (coating thickness) is between 1-2 mm, the potential difference of the electrode is the smallest, the deintercalation and mass transfer efficiency of lithium ions is high, and the adsorption capacity of the cathode for lithium ions (lithium extraction amount) is also high.

[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A cathode for an electrodialysis device, characterized in that: It includes a conductive substrate and an electrode material arranged on the surface of the conductive substrate; The conductive matrix is ​​three-dimensional graphene; the electrode material is a composite metal aluminate that has been hydrothermally treated, and the raw materials for preparing the composite metal aluminate include a soluble aluminum source, a soluble salt, and a precipitant; wherein the cation of the soluble salt is Mn 2+ Mg 2+ 、Na + And Ni 2+ Any one of .

2. The cathode for an electrodialysis device according to claim 1, characterized in that: The molar ratio of the metal ions in the soluble salt to the aluminum ions in the soluble aluminum source is 1:4-3:1, the precipitant is a mixture of sodium hydroxide and sodium carbonate, wherein the molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to aluminum ions in the soluble aluminum source is 8:1; In the cathode for an electrodialysis device, the thickness of the electrode material is 1-2 mm.

3. The method for preparing a cathode for an electrodialysis device according to any one of claims 1 to 2, characterized in that: The steps include: S1: performing two oxidation treatments on graphite powder to prepare three-dimensional graphene; S2: preparing the three-dimensional graphene prepared in step S1 into a conductive substrate; S3: preparing a first mixed solution with a soluble aluminum source, a soluble salt, a precipitant and water, and then heating the first mixed solution to obtain a composite metal aluminate; then hydrothermally treating the composite metal aluminate prepared in step S3, cooling and washing, to obtain a hydrothermally treated composite metal aluminate; S4: The hydrothermally treated composite metal aluminate prepared in step S3 is mixed with a binder, a conductive material and a solvent to prepare a slurry, and then the slurry is coated on the surface of the conductive substrate prepared in step S2, and after drying, a cathode for an electrodialysis device is obtained.

4. The method for preparing a cathode for an electrodialysis device according to claim 3, characterized in that: The above step S1 specifically includes: S11: adding concentrated sulfuric acid to a mixture of K2S4O8 and P2O5, adding graphite powder to the mixed system under stirring, performing a first oxidation reaction, cooling, washing, and drying after the reaction to obtain a pre-oxidized product; S12: adding the pre-oxidized material into concentrated sulfuric acid, uniformly dispersing the pre-oxidized material, and then adding potassium permanganate for a second oxidation reaction. Then, adding the first portion of deionized water, heating and stirring, and sequentially adding hydrogen peroxide solution and the second portion of deionized water to obtain a crude product. S13: extracting, washing, and drying the crude product to obtain three-dimensional graphene.

5. The method for preparing a cathode for an electrodialysis device according to claim 3, characterized in that: The above step S2 specifically includes: S21: dissolving the first binder in an organic solvent to obtain a second mixed solution, then adding the three-dimensional graphene prepared in step S1 to the second mixed solution and stirring until the organic solvent is completely volatilized to obtain a solid precursor; wherein the first binder is ethyl cellulose and the organic solvent is acetone; S22: placing the solid precursor in a protective atmosphere, heat treating it at 750-850° C. for 1.5-2.5 h, and obtaining a conductive matrix precursor after cooling; S23: removing impurities, cleaning and drying the conductive substrate precursor to obtain a conductive substrate.

6. The method for preparing a cathode for an electrodialysis device according to claim 3, characterized in that: The above step S3 specifically includes: S31: dissolving a soluble salt, a soluble aluminum source and a precipitant in water to obtain a first mixed solution; wherein the molar ratio of metal ions in the soluble salt to aluminum ions in the soluble aluminum source is 1:4-3:1, the precipitant is a mixture of sodium hydroxide and sodium carbonate, the molar ratio of sodium hydroxide to sodium carbonate is 16:1, and the molar ratio of sodium hydroxide to aluminum ions in the soluble aluminum source is 8:1; S32: placing the first mixed solution prepared in step S31 at 90-100° C. for heating and reacting for 1.5-2.5 hours, and drying after the reaction to obtain a composite metal aluminate; S33: Mix the composite metal aluminate prepared in step S3 with a sodium hydroxide solution, adjust the pH of the mixed system to 13-14, and then allow the mixed system to hydrothermally react at 150-170° C. for 18-30 hours, cool and wash to obtain a hydrothermally treated composite metal aluminate.

7. The method for preparing a cathode for an electrodialysis device according to claim 3, characterized in that: The above step S4 specifically includes: S41: dissolving the second binder in a solvent to obtain a mixed solution, then adding the hydrothermally treated composite metal aluminate and the conductive material to the mixed solution, and stirring evenly to obtain a slurry; the mass ratio of the second binder, the conductive material and the hydrothermally treated composite metal aluminate is (1-2):(1-2):(8-10); wherein the second binder is polyvinylidene fluoride, the solvent is N-methylpyrrolidone, and the conductive material is carbon black; S42: The slurry is evenly coated on the surface of the conductive substrate, and dried for 8-12 hours to obtain a cathode for an electrodialysis device.

8. An electrodialysis device, characterized in that: The invention comprises the cathode for an electrodialysis device according to any one of claims 1 to 2 or the cathode for an electrodialysis device prepared by the preparation method according to any one of claims 3 to 7.

9. The electrodialysis device according to claim 8, characterized in that It also includes an anode, a concentration chamber partition and a desalination chamber partition are arranged between the anode and the cathode, a cation exchange membrane and an anion exchange membrane are arranged on both sides of the concentration chamber partition, and an anion exchange membrane and a cation exchange membrane are arranged on both sides of the desalination chamber partition, and adjacent concentration chamber partitions and desalination chamber partitions share the same anion exchange membrane or cation exchange membrane; The number of the concentration chamber partition and the number of the desalination chamber partition are both one.

10. Use of the cathode for an electrodialysis device according to any one of claims 1 to 2 or the cathode for an electrodialysis device prepared by the preparation method according to any one of claims 3 to 7 in extracting lithium from salt lake brine.

Citation Information

Patent Citations

  • Improved graphene oxide preparation method

    CN106915741A

  • Method for preparing N and S codoped three-dimensional graphene material by hydro-thermal method

    CN107416800A

  • Preparation method of 3D graphene oxide

    CN107673344A

  • Uniformly dispersed ultra-small metal nanoparticle material and dispersion method thereof

    CN111554929A

  • Self-supporting three-dimensional graphene oxide / polyaniline / carbon quantum dot electrode material

    CN114242468A